POTENCIAL DE GERAÇÃO DE BIOGÁS DE GENÓTIPOS DE BATATA-DOCE - Batista, Samantha de Paula (2018)
Biogas is a technology that enables the generation of energy through the process of anaerobic biodigestion, and the production from sweet potato is as option as an energy source. The present research had the objective of evaluating the biogas production in anaerobic biodigesters and characterizing the parameters morphoagronomic and physico-chemical composition of sweet potato cultivars BRS Cuia and BRS Rubissol and the genotypes Bela Vista and Laranjeiras. Initialy, a field experiment was conducted in a randomized complete block design, with four genotypes and three random replicates. After the harvest the genotypes were separated into two groups for the characterization: of aerial part and of tuberous roots. The results of the total average production was 10,036.1 kg ha-1 for the genotype Laranjeiras, 10,754.1 kg ha-1 for the cultivar BRS Cuia, which demonstrated high productive potential. For BRS Rubissol it was 6,684.7 kg ha-1 and 1,473.6 kg ha-1 for the Bela Vista genotype. In the physicochemical analyzes of the composition, it was verified that there were significant differences between the genotypes, in the local environmental conditions, with influence on the absorption of moisture, decomposition, occurring variations in the yield and quality of tuberous roots. For the biochemical methane potential (BMP) assays for homogeneity, the genotypes were processed in the form of flour to facilitate the process of anaerobic biodigestion. The biogas production estimate was 2,906.5 liters ha-1 for the cultivar BRS Cuia and 2,712.4 liters ha-1 for the Laranjeiras, BRS Rubissol was 2,906.5 liters ha-1 and for the Bela Vista it was 398,2 liters ha-1. The analysis of principal components (ACP) with biogas production of sweet potato genotypes, physicalchemical and agronomic parameters, showed all genotypes have a direct correlation with the amount of reducing sugars (ACP1 57.50%) and humidity (ACP2 40.27%), with 97.77% of the data variability explanation. The Laranjeiras genotype has the most significant potential to produce biogas, followed by BRS Cuia cultivar. In view of the obtained results, it is emphasized the sweet potato crop as a source of biomass for the energy generation.